Relationship Of Nutritional Family Concerned Behavior Stunting Events In Children - Hamdana; Tenriwati; Erni (Jurnal Life Birth, 2018)
According to WHO (World Health Organization) data, it is reported that globally the number of stunted children under the age of 5 is 165 million, 26%. Asia is the second region even higher after Africa which has the highest prevalence of stunting children, 26.8% or 95.8 million children, while the prevalence of stunting children in Southeast Asia is 27.8% or 14.8 million children.This research is an observational analytic study with a cross-sectional approach that aims to analyze the Relationship of Nutrition Conscious Family Behavior and Stunting Occurrence in Toddlers in the Bontonyeleng Community Health Center. The population in this study were children under five years old who were in the Bontonyeleng Public Health Center working area, Gantarang District, Bulukumba Regency, as many as 84 respondents. Data analysis used an alternative Kolmogorov chi-square test with p-value (<0,000). The results showed that the nutrition-conscious family behavior was 20 respondents (40.0%), while those who were not nutritionally conscious were 30 respondents (60.0%). From the results of short stunting 31 respondents (62.0%) were very short as many as 7 respondents (14.0%), and normal stunting were 12 respondents (24.0%). The conclusion that there is a relationship between Nutritional Conscious Family Behavior and Stunting Occurrence in Toddlers in the Bontonyeleng Community Health Center in Bulukumba Regency. It is suggested that the results of this study can be used as scientific reading material in the library and can also be used as reference material for students who are researching similar problems.